Physical Activity and Survival in Women With Advanced Breast Cancer. Issue 4 (July 2018) - Palesh, Oxana; Kamen, Charles; Sharp, Susan; Golden, Ashleigh; Neri, Eric; Spiegel, David; Koopman, Cheryl
Abstract : Background: Several empirical investigations have attempted to characterize the effect of physical activity on cancer mortality, but these investigations have rarely focused on patients with advanced breast cancer. Objective: The current study examined the hypothesis that greater physical activity is associated with longer survival among women with advanced breast cancer. Methods: We conducted a secondary data analysis of a prospective study of 103 patients with stage IV (n = 100) or locally recurrent (n = 3) breast cancer involved in a group psychotherapy trial. Physical activity was assessed at baseline using the Seven-Day Physical Activity Recall questionnaire, and patients were followed until April 1, 2016, at which time 93 of 103 had died. Results: Greater physical activity level at baseline was significantly associated with longer subsequent survival time in a Cox proportional hazards model (hazard ratio [HR], 0.90; 95% confidence interval [CI], 0.84–0.97; P < .01). Engaging in 1 additional hour per day of moderate activity reduced the hazard of subsequent mortality by 23% (HR, 0.77; 95% CI, 0.65–0.92; P < .01). These results remained significant even after controlling for demographic, medical, cancer, depression, and cortisol variables (HR, 0.91; 95% CI, 0.84–0.99; P < .05). Conclusions: Women with advanced breast cancer who engaged in physical activity for 1 or more hours per day at baseline had an increased likelihood of survival compared with those who exercised less than 1 hour per day. Implications for Practice: Nurses should consider recommending moderate physical activity for women with advanced breast cancer. Randomized trials of physical activity interventions for this population are needed.